Room temperature magnetoimpedance of La0.67Sr0.33–xPbxMnO3 (x = 0–0.33) manganites. (1st February 2019) - Biswas, Sonali; Keshri, Sunita
ABSTRACT: The present paper is focused on the study of different physical properties, especially magnetoimpedance (MI) ofL a 0.67 S r 0.33 − x P b x Mn O 3 ( x = 0–0.33) manganites of the rhombohedral structure. From the results of transmission electron microscopy it is evident that the average grain size lies in the range of 35–50 nm. MI measurements were carried out at room temperature for the frequency range of100 Hz − 10 MHz in presence of dc magnetic field of50 Oe − 9 kOe . The experimental results show that MI increases with the increase in grain size; the maximum MI (− 75 % ) and a large ac MR (− 90.5 % ) have been obtained for thex = 0.15 sample under a field of9 kOe at a frequency of100 kHz . However, the same sample shows very low dc MR (− 4.8 % ) under the same field. The MI results can be explained well in the light of skin depth effect and variation of transverse permeability with frequency.